Climate Change, Urbanization, and Zoonotic Diseases: A Narrative Review for Public Health Resilience - Umar, Fadly (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2024)
Climate change and urbanization are intensifying the emergence of zoonotic diseases, posing urgent challenges to public health systems—particularly in rapidly growing urban areas. This narrative review examines the interplay between climate variability, environmental change, and zoonotic disease transmission, focusing on temperature shifts, precipitation patterns, and urban land-use dynamics. A systematic literature review was conducted to synthesize empirical studies across diverse climatic and urban contexts. Findings reveal that rising temperatures accelerate pathogen replication and expand vector habitats, while altered rainfall patterns increase the likelihood of waterborne and vector-borne disease outbreaks. Urbanization-induced deforestation, habitat fragmentation, and inadequate infrastructure further heighten human-wildlife interactions and disease spillovers. Vulnerabilities are exacerbated in low-income communities with limited access to sanitation, healthcare, and early warning systems. This review highlights the urgent need for integrative public health strategies and climate-adaptive urban planning to mitigate zoonotic risks. Policymakers must prioritize early surveillance, equitable health access, and ecosystem-sensitive development. By adopting the One Health framework and strengthening interdisciplinary collaboration, cities can build resilience to future zoonotic threats in the context of accelerating climate change.